An Analysis of Students’ Speech Act as Foreign Language Learners in A Speaking Class - Djafar, Hariyanti; Wahid, Jusmin HJ. (International Journal of Education, Information Technology, and Others, 2025)
In the speech act of non-native speakers' speech, it takes its own effort. In addition to the anticipation of nervousness in speaking a foreign language, expressions and gestures can also cover grammar errors, although errors in grammar but the intention can be conveyed to the interlocutor. This paper aims to explore the ways in English Foreign students speak and their negotiations to convey their intentions to each other through conversations. The subjects of this study consisted of 15 English language learners at Muhammadiyah University of North Maluku. The data were categorized into 6 speech act situations including; (Negligence of not making assignments, Greetings, Congratulations, Parting, Excuses, and Thanking) where these occurred naturally and were taken during communication both orally and in writing among students and lecturer. Finally, the paper reveals that researching oral or written speech act performance are noted and is recognized as one of the difficulties in linguistics researcher. It is said to be difficult in linguistics because it must consider situations, expressions, and gestures to convey and understand meaning. The result shows how explicit students as foreign language learners In the conclusion, analysing a speech act in a language are first realized about not only the actions but also the situation behind what speaker and interlocutor were talking.